Chinese herb medicine against Sortase A catalyzed transformations, a key role in gram-positive bacterial infection progress. (1st November 2016) - Si, Lifang; Li, Pan; Liu, Xiong; Luo, Lixin
Abstract: Many Gram-positive bacteria can anchor their surface proteins to the cell wall peptidoglycan covalently by a common mechanism with Sortase A (SrtA), thus escaping from the host's identification of immune cells. SrtA can complete this anchoring process by cleaving LPXTG motif conserved among these surface proteins and thus these proteins anchor on the cell wall. Moreover, those SrtA mutants lose this capability to anchor these relative proteins, with these bacteria no longer infectious. Therefore, SrtA inhibitors can be promising anti-infective agents to cure bacterial infections. Chinese herb medicines (CHMs) (chosen from Science Citation Index) have exhibited inhibition on SrtA of Gram-positive pathogens irreversibly or reversibly. In general, CHMs are likely to have important long-term impact as new antibacterial compounds and sought after by academia and the pharmaceutical industry. This review mainly focuses on SrtA inhibitors from CHMs and the potential inhibiting mechanism related to chemical structures of compounds in CHMs.